Filling in the blanks : understanding standardized testing and the black-white test score gap - Arbuthnot, Keena (Contemporary perspectives in race and ethnic relations., 2011)
Filling in the Blanks is a book dedicated to helping policymakers, researchers, academics and teachers, better understand standardized testing and the Black-White achievement gap. This book provides a wealth of background information, as well as the most recent findings, about testing and measurement concepts essential to understanding standardized tests. The book then reviews theories and research that has been conducted which explain the differences in performance between Black and White test takers on many standardized tests. Most notably, Filling in the Blanks presents several new theories that address why Black students do not perform as well as their White counterparts. These theories present very novel and innovative perspectives to understanding these test performance differences. The book ends with a host of recommendations that are intended to address the concerns and questions of several stakeholder groups.